Synthesis and Characterizations of CH3NH3PbI3 : ZnS Microrods for Optoelectronic Applications - Mohammad Tanvir Ahmed; Shariful Islam; Muhammad Shahriar Bashar; Md. Abul Hossain; Farid Ahmed (Advances in Materials Science and Engineering)
Organometallic perovskite is one of the potential materials in the various optoelectronic research fields. This study demonstrates the synthesis of CH3NH3PbI3 : ZnS microrods via one-step spin coating for optoelectronic applications. Incorporation of ZnS in the perovskite material caused bandgap variation in the visible wavelength range. Structural and chemical properties have been observed using X-ray diffraction, scanning electron microscope, and Fourier transform infrared spectroscopy. The optical and electrical properties were studied via UV-Vis spectroscopy and impedance analyzer. The addition of ZnS caused to increase the optical absorption coefficient from ∼104 cm−1 to ∼105 cm−1. The bandgaps of the thin films were calculated using the Tauc relation and electrical method, obtained in the range 1.51 eV–1.64 eV, suitable for various optoelectronic applications.